Producing ratio measures of effect with quantitative microbial risk assessment. Issue 5 (10th June 2022) - Capone, Drew; Bivins, Aaron; Brown, Joe
Abstract: Estimating the risk of infections or other outcomes incident to pathogen exposure is a primary goal of quantitative microbial risk assessment (QMRA). Such estimates are useful to predict population‐level risks, to evaluate exposures based on normative or tolerable risk guidelines, and to interpret the likely public health relevance of microbial measurements in environmental media. To evaluate alternative control measures (interventions), ratio estimates of effect (e.g., odds and risk ratios) are needed that are more broadly interpretable in the health sciences and consistent with convention in epidemiology. In this paper, we propose a general method for estimating widely used ratio measures of effect derived from stochastic QMRA approaches, including the generation of appropriate confidence intervals. Such QMRA‐derived ratios can be used as a basis for evaluating interventions via hypothesis testing and for inclusion in systematic reviews and meta‐analyses in a form consistent with risk estimation approaches commonly used in epidemiology.